Carbon monoxide activation and poisoning on metallic and enzymatic sites: a new ATR-IR spectroelectrochemical approach - Chang, G (2016)
Direct liquid fuel cells (DLFCs) offer a great opportunity to replace traditional fuel combustion with cleaner localised energy production. One of the biggest challenges for developing a commercial DLFC device is the production of CO during fuel oxidation. CO is not only one of the most common intermediates of hydrocarbon fuels oxidation but also a poison of most metal catalysts. In situ infrared (IR) spectroelectrochemical (SEC) techniques have been intensively used to understand the reaction mechanisms for oxidation of different fuels and to study the presence and activation of CO on different bulk metal electrodes. However, there have been few studies of supported nanocatalysts during electrocatalytic turnover relevant to realistic fuel cell devices. In this Thesis, a new attenuated total reflectance IR (ATR-IR) SEC approach is used to study the electrocatalytic oxidation of formic acid and methanol on a commercial carbon supported Pd nanocatalyst (Premetek, USA, 60% Pd / XC-72). The results from ATR-IR SEC studies of formic acid oxidation on the Pd nanoparticles show CO poisoning, and reveal that this is derived from trace organic impurities present in reagent grade formic acid, rather than from the dehydration of formic acid itself. The supported Pd catalyst shows very different activities for methanol oxidation in different pH conditions. In acidic conditions, the catalyst is strongly poisoned by adsorbed CO and shows very low activity towards methanol oxidation. On the other hand, in alkaline conditions, only very weak IR signal from adsorbed CO can be detected and the activity of methanol oxidation is much higher compared to the acidic conditions. The detection of strong IR signals from formate suggests that formate acts as a significant reactive intermediate. In the final part of this Thesis, the possibility of developing a more efficient electrocatalytic system to reduce greenhouse gas carbon dioxide to hydrocarbon feedstocks is demonstrated by using a composite catalyst which comprises an enzyme to reduce CO2 to CO, and copper nanoparticles for further reduction of CO. Overall this Thesis provides insight into the activation of CO at metal sites during electrocatalytic reactions which are relevant to energy technologies.